The effects of antibiotics and melatonin on hepato-intestinal inflammation and gut microbial dysbiosis induced by a short-term high-fat diet consumption in rats - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
High-fat diet (HFD) consumption leads to metabolic disorders, gastrointestinal dysfunction and intestinal dysbiosis. Antibiotics also disrupt the composition of intestinal microbiota. The aim of the present study was to investigate the impact of a short-term feeding with HFD on oxidative status, enteric microbiota, intestinal motility and the effects of antibiotics and/or melatonin treatments on diet-induced hepato-intestinal dysfunction and inflammation. Male Sprague-Dawley rats were pair-fed with either standard chow or HFD (45 % fat) and were given tap water or melatonin (4 mg/kg per d) or melatonin plus antibiotics (ABX; neomycin, ampicillin, metronidazole; each 1 g/l) in drinking water for 2 weeks. On the 14th day, colonic motility was measured and the next day intestinal transit was assessed using charcoal propagation. Trunk blood, liver and intestine samples were removed for biochemical and histopathological evaluations, and faeces were collected for microbiota analysis. A 2-week HFD feeding increased blood glucose level and perirenal fat weight, induced low-level hepatic and intestinal inflammation, delayed intestinal transit, led to deterioration of epithelial tight junctions and overgrowth of colonic bacteria. Melatonin intake in HFD-fed rats reduced ileal inflammation, colonic motility and perirenal fat accumulation. ABX abolished increases in fat accumulation and blood glucose, reduced ileal oxidative damage, suppressed HFD-induced overgrowth in colonic bacteria, and reversed HFD-induced delay in intestinal transit; however, hepatic neutrophil accumulation, hepatic injury and dysfunction were further enhanced. In conclusion, the results demonstrate that even a short-term HFD ingestion results in hepato-intestinal inflammatory state and alterations in bacterial populations, which may be worsened with antibiotic intake, but alleviated by melatonin.
Keywords: High-fat diet; Microbiota; Oxidative injury; Antibiotics; INDUCED OBESITY; INSULIN-RESISTANCE; METABOLIC SYNDROME; BODY-WEIGHT; MODULATION; ADAPTATION; PROTECTS; DAMAGE; INJURY; REPERFUSION